Ancient Wheat Diet Delays Diabetes Development in a Type 2 Diabetes Animal Model (The Review of Diabetic Studies, 2023)
AIM: The main objective was to investigate the physiological effects of ancient wheat whole grain flour diets on the development and progression of type 2 diabetes in Zucker diabetic fatty rats, and specifically to look at the acute glycemic responses. METHODS: An intervention study was conducted, involving 40 ZDF rats consuming one of 5 different diets (emmer, einkorn, spelt, rye and refined wheat) for 9 weeks. Refined wheat flour and whole grain rye flour were included as negative and positive controls, respectively. RESULTS: After 9 weeks of intervention, a downregulation of the hepatic genes PPAR-α, GLUT2, and SREBP-1c was observed in the emmer group compared to the control wheat group. Likewise, expression of hepatic SREBP-2 was lower for emmer, einkorn, and rye compared with the control group. Furthermore, spelt and rye induced a low acute glycemic response. The wheat group had higher HDL- and total cholesterol levels. CONCLUSIONS: Ancient wheat diets caused a downregulation of key regulatory genes involved in glucose and fat metabolism, equivalent to a prevention or delay of diabetes development. Spelt and rye induced a low acute glycemic response compared to wheat.